2022
DOI: 10.1186/s40729-022-00464-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of immediate implant placement using static and dynamic computer-assisted implant system in the esthetic zone of the maxilla: a prospective study

Abstract: Purpose This study aimed to compare the accuracy of fully guided between dynamic and static computer-assisted implant surgery (CAIS) systems for immediate implant placement in the esthetic zone. Methods A total of 40 qualified patients requiring immediate implant placement in the esthetic zone were randomly and equally assigned to either static CAIS group (n = 20) or dynamic CAIS groups (n = 20). Global deviations at entry, apex, and angular deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…4 . Overall, the nineteen RCTs [ 12 , 22 , 26 , 42 , 54 , 59 , 64 66 , 69 , 72 , 74 77 , 79 82 ] were assessed using RoB-2. Nine presented a “low risk” of bias, while eight presented “some concerns”.…”
Section: Resultsmentioning
confidence: 99%
“…4 . Overall, the nineteen RCTs [ 12 , 22 , 26 , 42 , 54 , 59 , 64 66 , 69 , 72 , 74 77 , 79 82 ] were assessed using RoB-2. Nine presented a “low risk” of bias, while eight presented “some concerns”.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the DN has been increasingly used to assist surgeons to improve the precision of surgery [ 9 , 10 ]. Studies have indicated that the accuracy of DN is similar to that of a static guide in assisting implant placement [ 17 19 ], and both of which are better than that of the free hand [ 20 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic navigation (DN) has been applied in implant surgery as an effectively preventative measure to reduce the deviation of implant placement [ 9 , 10 ]. DN can consistently track the 3D real-time position of the implant drills and sinus floor combined with imported Cone-beam computed tomography (CBCT) data, enable safe and accuracy location of the entry point and visualize implant placement as the planned position.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely utilized MPR strategy when performing dental implant placement relies on the utilization of a U‐shaped tube device (Feng et al., 2022; Liu et al., 2022; Ma et al., 2022; Wei et al., 2022; Wu, Ma, & Sun, 2023; Wu, Xue, et al., 2023; Xu et al., 2023; Yan et al., 2023). Nevertheless, a novel approach has been devised wherein a dual‐purpose registration‐and‐fixation apparatus was developed, incorporating three reflecting patches (Wu & Sun, 2022).…”
Section: Introductionmentioning
confidence: 99%